Evaluating factors influencing pregnancy in beef cows and evaluating factors at weaning influencing ability to pass breeding soundness examination in beef bulls - Fountain, Tara (Kansas State University, 2020)
The common thread of this research was to identify factors that improve efficiency and subsequent profitability for cow-calf producers. The objective of the literature review was to evaluate factors, such as nutrition, breed, season of birth, exposure to cycling females and hormones that influenced puberty in peri-pubertal bulls. Finding factors that influence puberty are important for both for seedstock producers and commercial cattlemen. Bulls that attain puberty earlier have a higher likelihood of passing the breeding soundness examination by the time of marketing. The objective of the first study was to determine if factors such as herd size, breeding season length, body condition of cow at mid-gestation, or the timing of breeding season affected the likelihood of pregnancy at the end of the first 21-day interval and at the end of the breeding season. Data were collected by convenience sampling from herds (n=241) consisting of 8,217 head located in the Midwest and Great Plains regions of the US from 2012 to 2017. Pregnancy diagnosis data were recorded in either 20- or 21-day intervals. A logistic regression model was used to evaluate the effect of the relevant factors (herd size category, breeding season length category, body condition score category, and timing of breeding season category) on the probability of pregnancy status at two different time-points (21-day and end of breeding season). Overall, an average 53.6% of cattle across all herds were pregnant by the end of the first 21-day interval, and an average 85.2% of cattle across all herds were pregnant by the end of the breeding season. Herds with short or medium breeding season lengths (<63 days or 63-84 days) had increased probability of pregnancy (65% and 58%, respectively) for the first 21-day interval compared to herds with a long breeding season (49%). Cows in thin body condition at the time of pregnancy diagnosis had reduced probability of having become pregnant during both the first 21-day interval (44%) and the entire breeding season (64%) when compared to cows in moderate (62%, 86%) and fleshy (66%, 91%) condition. Herds with less than 50 head had reduced probability of pregnancy (51%, 78%) as compared to medium sized (50-99 head) herds (63%, 84%) for both the 21-day interval and overall breeding season. Herds that started the breeding season in the fall had higher probability of pregnancy at the end of the breeding season (88%) as compared to spring start dates (82%). Management factors such as breeding season length, body condition score, herd size, and timing of breeding season had significant impacts on the probability of pregnancy. In the future, more research needs to be conducted to evaluate the economic impacts of these management choices. The focus of the next study was identifying bulls at a young age with higher likelihood of passing a breeding soundness examination as yearlings. Finding these bulls at weaning may improve management options to optimize production efficiency and profitability. The objective of this study was to evaluate the effect of weaning scrotal circumference and other factors collected at the time of weaning on the likelihood of passing a breeding soundness examination as a yearling. Data, at both weaning and time of breeding soundness examination, were collected from one operation (n = 466 bulls). A logistic regression model was used to evaluate the potential associations of relevant factors (actual weaning scrotal circumference, adjusted weaning scrotal circumference, weight per day of age at weaning, scrotal circumference per day of age at weaning, weaning weight, days of age and breed) on the probability of passing a breeding soundness examination as a yearling. Overall, 92.3% of bulls passed the yearling breeding soundness examination on first evaluation. Weaning scrotal circumference was the only factor of those evaluated associated (P < 0.01) with the probability of passing the breeding soundness examination. No significant differences were found between the categories of weaning scrotal circumference. Bulls with weaning scrotal circumference over 31 cm had the lowest probability (80.9%) of passing the yearling breeding soundness examination, but was not statistically significant. Breed was not associated (P = 0.53) with the probability of passing the breeding soundness examination. In the future, more research needs to evaluate predictive model development for weaning scrotal circumference and ability to pass breeding soundness examination.
Keywords: Efficiency; Fertility; Breeding Soundness Examination; Pregnancy Interval